Pattern of Aging Transition in Nepal: A New Sociological Perspective - Khanal, Kashi Nath (Interdisciplinary Journal of Management and Social Sciences, 2024)
Aging has been a key social phenomenon based on demographic transition, which is powered by the decrease of birth and death rates, and an increase of life expectancy at birth. It in the recent times has been highly successful in drawing more serious attention of an intellectual circle across the world. Society often considers aging as a problem that creates serious imbalances in a social system, but the condition of aging people and the impact of aging differs depending on the countries. Thus, the situation of aging people in Nepal drastically differs from aging people in other industrialized countries. Notwithstanding ageism a serious social problem, this paper describes only the transition in the structure and pattern of aging people that has taken place in the last seven decades in Nepal. It further makes an advocacy of different sociological perspectives to study aging in Nepalese context. Aging people in Nepal are living at risk, but the risks they have faced are far less compared to the aging people in real world-scenario.